THE APPLICATION OF DRY RUBBER LATEX AND VERMICOMPOST TO PLANT WATER CONSUMPTION AND THE GROWTH OF PADDY ON SWAMPY LAND - Irmawati, Widya; Bernas, Siti Masreah; Bakri , Bakri (BIOVALENTIA: Biological Research Journal, 2021)
Swampy land is an alternative for rice plant cultivation where the amount of rainfall has an impact on the amount of inundation. In order to provide appropriate water for rice plants, especially during the dry season, an irrigation water system is required for its control.Alternative materials such as dry rubber latex and vermicom-post can be utilized to reduce water use and ensure that water is delivered as efficiently as possible. The goal of this study was to see how dried rubber latex on the soil surface and vermicompost in the soil affected rice plant water demand and growth. This research was conducted from November 2020 – February 2021. The study used a factorial randomized block design (RAKF) with 2 treatments, covered dry rubber latex variations (K), K0 (0%), K1 (25%), K2 (50%), K3 (75%), and vermicompos (V), V0(0 g), V1(58.82 g), V2(117.64 g), V3 (176.46 g)with 3 rep-licat. So that the total treatmentsare 48 treatments.The results showed that the application of dry rubber latex and vermicompost significantly affected the number of leaves and the number of tillers. The K3 treatment (75%) was the best because it had the smallest evapotranspiration rate with an average of 1.2 mm day-1. The K3 treatment (75%) had the smallest average water requirement of 1.6 mm day-1 with an average number of 37.07 leaves. The high yield of K3 treatment was due to the wider the area covered by 75% (K3), the higher the water content, nutrients, and the lower the soil temperature. Closure using dry rubber latex can reduce sunlight so that the process of water loss is lower, and the available nutrients are higher.